Pengetahuan dan Sikap Warga Negara Muda Terhadap Kebijakan Pandemi Covid-19 - Saputra, Meidi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to analyze the knowledge and attitudes of young citizens before and after the Covid-19 pandemic policy. This study uses a quantitative approach with a comparative survey method. The sample in this study was 376 students who were spread proportionally in East Java. Data collection was carried out using a questionnaire or questionnaire technique. The data that has been obtained is analyzed using descriptive techniques and displayed in the form of bar graphs. The results of the study show that the knowledge of young citizens is quite good, as evidenced by the reduction in the category of unfavorable from 5.1 percent before the policy was introduced to 3.4 percent after the policy was implemented. The attitude of young citizens who disagree with the Covid-19 pandemic policy has increased starting from the implementation of health protocols, prohibition of activities in public places, a sense of responsibility for the safety of the community, responses to seeing people not wearing masks, feeling guilty if they don’t comply with health protocols, sanctions for violators of health protocols, transparency regarding information regarding the Covid-19 pandemic, and granting equal rights to Covid-19 services.